2011
DOI: 10.1016/j.visres.2010.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Visual deficits in anisometropia

Abstract: Amblyopia is usually associated with the presence of anisometropia, strabismus or both early in life. We set out to explore quantitative relationships between the degree of anisometropia and the loss of visual function, and to examine how the presence of strabismus affects visual function in observers with anisometropia. We measured optotype acuity, Pelli-Robson contrast sensitivity and stereoacuity in 84 persons with anisometropia and compared their results with those of 27 persons with high bilateral refract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
93
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 48 publications
5
93
0
6
Order By: Relevance
“…It is well known that neurotransmitters are active players for retinal responses. In this study P50 and N95 wave amplitudes of pERG were decreased significantly in eyes with ambylopia whereas latency periods were not statistically different than the contralateral eyes [27][28][29][30] .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is well known that neurotransmitters are active players for retinal responses. In this study P50 and N95 wave amplitudes of pERG were decreased significantly in eyes with ambylopia whereas latency periods were not statistically different than the contralateral eyes [27][28][29][30] .…”
Section: Discussionmentioning
confidence: 93%
“…Levi et al [27] reported that decrease of P100 amplitude in eyes with amblyopia were caused by cortical neurons which get less impulse from the eyes with amblyopia. Prolonged pVEP latency periods of eyes with amblyopia may be related with prolonged conduction between retina and cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the investigations focused on the stereoacuity, contrast sensitivity, accommodation and convergence, and interocular suppression of anisometropic patients. [14][15][16][17][18][19][20][21][22] In this retrospective study, the PEP among patients with different degrees of anisometropia were compared to elucidate whether PEP deviation was associated with the development of anisometropia. We found that the deviation of vertical PEP in patients with interocular SE difference ≥2.50D was much higher than that in patients with interocular SE difference <2.50D.…”
Section: Discussionmentioning
confidence: 99%
“…The association between increasing anisometropia and decreasing binocular function has been convincingly shown by artificially induced anisometropia in normal subjects. [14][15][16][17][18][19][20][21][22] Perceptual eye position (PEP) is a new concept describing binocular alignment raised by Zhao et al in 2014. [23] It is one of the indicators used to evaluate fixation disparity and binocular function measured by a computer-controlled perceptual examination evaluation system.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the abnormal functions of the binocular vision due to ametropia, anisometropia, horizontal-vertical phoria, fixation disparity and age related ocular dysfunctions. [1][2][3][4][5][6][7][8][9][10] These factors affect stereo acuity and differences in stereo acuity exist acuity among the people who are not stereo-blind.…”
Section: Introductionmentioning
confidence: 99%